PENYULUHAN 1000 HPK DAN GIZI SEIMBANG PADA IBU BALITA DI POSYANDU KEMBANG MATAHARI, MARGAHAYU, BEKASI - Sartika, Arindah Nur; Noerfitri, Noerfitri; Puspitadewi, Amaliafani (Universitas Mataram, 2024)
The first thousand days of life/Golden Period / window of opportunity is a crucial phase of life. 1000 days of life starts in the womb until the child is 2 years old. Nutritional problems that occur in this phase include anemia and stunting. The problems above are nutritional problems that need to be addressed, one of which is by understanding the urgency of 1000 HPK and balanced nutrition. This activity is aim to increase knowledge is carried out in the form of nutrition education. Before the activity, a pre-test was carried out and ended with a post-test at the end of the activity. The success of this activity is concluded by evaluating the pre-test and post-test scores. Of the 35 participants who attended, only 17 participants completed the pre-test and post-test. This was because there were participants who arrived late or did not participate in the activity until the end. The average pre-test score is 7.94 and the average post-test score is 11.24. . There was an increase in scores on the post-test of 3.3 points. Statistical analysis using the paired t-test revealed that the increase in knowledge value occurred significantly (p-value < 0.05). This community service activity succeeded in increasing participants' knowledge with several supporting factors, including the use of appropriate media, appropriate delivery methods, and adequate time. This activity was successfully carried out and there was a significant increase in participants' knowledge. It is hoped that the increase in knowledge that occurs can change the attitudes and behavior of activity participants so that they implement a balanced nutritional diet in their daily lives.